Design of a Hydrodynamic Profile for an Unmanned Underwater Device Using Numerical Simulation - Tocón, Axl (2022)
The present work proposes the design of a hydrodynamic profile for unmanned submarine devices through numerical simulation, thus facilitating experimental studies and reducing manufacturing costs. Design and manufacturing aspects of different authors were studied to establish a highly maneuverable vehicle, capable of moving in the horizontal and vertical plane. For this reason, the final design proposes hydrodynamic profiles in the bow and stern using the “Myring” equations. It also has cross-shaped hydrodynamic fins located in the bow, which will help reduce the drag coefficient. Therefore, this work aims to study and analyze the hydrodynamic characteristics of the submarine using the ANSYS Fluent software. Likewise, the drag coefficient will be analyzed for different operating speeds, in order to know what is the maximum drag force that should be overcome to move at that speed. Finally, it was observed that the results obtained from the simulations are values quite similar to those obtained through hydrodynamic formulas or experimental tests.